SISTEM PAKAR DIAGNOSA GANGGUAN KEJIWAAN MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Yuliana Yuliana; Noviyanti Noviyanti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
According to WHO, mental health is a physical condition of a person's sense of well-being, so that there is the ability to manage the normal stresses of life, to be able to work productively and to complete task detecting a disease with a computer will make it easier for medical personnel and the public to determine conclusions in the form of solutions and handling. One form of technological progress is an expert system which is part of artificial intelligence by utilizing one method, namely forward chaining. This study uses the forward chaining method by providing information to diagnose 9 disease data and 22 symptom data accompanied by disease data, symptoms, explanations of types of diseases, causes, and solutions for patients. A web-based expert system can diagnose mental disorders so that patients can do digital consultations about their illnesses. Based on the results of the analysis on the system, data from the number of visitors showed that the percentage of respondents' answers was 98.99% already user friendly and responsive. And the results of system testing using black boxes show a 100% percentage, until it can be concluded that the expert system application is feasible to use.